Single Applications of Natural Postemergence Weed Control Options Do Not Provide Effective Ground Ivy Control. Issue 1 (30th May 2019) - Patton, Aaron J.; Braun, Ross C.; Weisenberger, Daniel V.
Abstract : Core Ideas: More information is needed on the turf safety and efficacy of over‐the‐counter natural weed control products. A single application of the tested natural weed control options will not control ground ivy. Homeowners and turf practitioners using natural weed control options will need to differentiate between selective products safe for turf and non‐selective products injuring turf before making a purchase/application. A frequent question is "What 'natural' or 'organic' herbicides (i.e., non‐pesticide products) are available for weed control in lawns"? The objectives of this experiment were to determine injury to Kentucky bluegrass ( Poa pratensis L.) and efficacy of various natural weed control products on ground ivy ( Glechoma hederacea L.). Thirteen "natural" or "organic" treatments were compared to a synthetic postemergence herbicide and a nontreated control. Products were applied in October 2010 and 2011 in West Lafayette, IN. Turf injury was highest for the flame thrower treatment for up to 4 weeks after treatment (WAT). Treatments including Scythe, Worry Free Weed and Grass Killer, BurnOut II Fast Acting Weed and Grass Killer, octanoic acid with or without clove oil, clove oil, and a vinegar cocktail resulted in unacceptable turf injury for 2 to 4 WAT, but then all treatments recovered by 4 to 6 WAT or the following spring. At 3 WAT, ground ivy was initially reduced (75 to 100% control) by the flame thrower, Scythe, BurnOut II Fast Acting Weed and Grass Killer, octanoic acid + clove oil, and mechanical weed control treatments. However, ground ivy coverage reductions were temporary, as a single fall application did not provide adequate long‐term control (>50%), and all treatments were similar the following spring, providing an average of only 22% ground ivy control. Single applications of the tested natural weed control options do not adequately control ground ivy with the majority of the products causing unacceptable turf injury.